Mortality Rates Of Adult Pulmonary Tuberculosis With Malnutrition: A Case Report And Comprehensive Literature Review - Muhammad Ilham Dhiya Rakasiwi; Astrid Mariam Khairani Siregar; Brayanna Infinita Laviashna Saputro; Fathiyah Isbaniah; Lily Indriani Octovia (Journal of Agromedicine and Medical Sciences, 2023)
Tuberculosis (TB) and malnutrition are still major public health problems in the world. These two clinical conditions can occur simultaneously and create a vicious cycle that worsens TB infection or nutritional status. This case report aims to examine the relationship between low nutritional status (malnutrition) of patients and death due to pulmonary TB. A 31 year old woman came to the pulmonary clinic of a tertiary hospital in Jakarta for her third month of drug-sensitive anti-TB drug (OAT) treatment control. Three months earlier, the patient underwent a rapid diagnostic test (RDT) to determine OAT resistance. The conclusion of her anthropometric examination was body mass index (BMI) of 15.6 kg/m2. Before being diagnosed with pulmonary TB, she always had difficulty gaining weight. During the course of disease, her weight decreased by 5 kg per month. After undergoing treatment for 6 months, the patient was declared complete after 6 months of therapy, without any improvement in nutritional status. At 1 year follow-up, the patient experienced a relapse of pulmonary TB with a BMI of 13.2 kg/m2. She died 2 months after diagnosis of relapse TB. Improvement in clinical complaints and conversion to bacteriological examination are indications of successful therapy, including improvement in nutritional status. To analyze the relationship between malnutrition and pulmonary TB and death, the authors conducted a comprehensive literature search in the journal databases PubMed, Cochrane, and Scopus, followed by analysis according to the PRISMA 2020 flowchart, for a prognostic cohort study of cases of death in pulmonary TB patients with malnutrition. There is a relationship between BMI and the risk of death in TB patients. Anthropometric measurements, especially BMI, need to be carried out during every physical examination of pulmonary TB cases. Keywords: Body mass index; Malnutrition; Mortality; Tuberculosis